2019
DOI: 10.3389/fimmu.2019.01754
|View full text |Cite
|
Sign up to set email alerts
|

The Kuwait National Primary Immunodeficiency Registry 2004–2018

Abstract: Objective: To present the report from the Kuwait National Primary Immunodeficiency Registry between 2004 and 2018. Methods: The patients were followed prospectively between January 2004 and December 2018 and their collected data included sociodemographic, diagnosis, clinical presentation, laboratory tests, and treatment. Results: A total of 314 PID patients (165 males and 149 females) were registered during the study period. Most of the patients ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 23 publications
23
41
2
Order By: Relevance
“…Organized registries represent an efficient and well-defined instrument for better characterization and understanding of rare diseases, with positive impact on the clinical management of affected patients and on the comprehension of the natural history of the disease [3,4]. In the last few decades, registries have been created for primary immunodeficiencies in several countries around the world in order to better define the distribution and features of patients affected with these disorders [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Organized registries represent an efficient and well-defined instrument for better characterization and understanding of rare diseases, with positive impact on the clinical management of affected patients and on the comprehension of the natural history of the disease [3,4]. In the last few decades, registries have been created for primary immunodeficiencies in several countries around the world in order to better define the distribution and features of patients affected with these disorders [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…(17.1%), Among patients molecular diagnosis was observed in 40.2% and parental consanguinity was recorded in 19.4%[34][35][36].During the last decade, other Asian PID cohorts have been reported containing fewer patients each. Al-Herz et al in 2019, published a registry report of 314 PID patients in Kuwait with the highest genetically solved rate of 69.1% with 78.0% paternal consanguinity (prevalence of PID 20.2 in 100000, predominantly antibody immunodeficiency of 17.8%)[37][38][39]. In 2013, Ehlayel et al have reported a single-center registry of 131 pediatric PID patients from Qatar with the lowest number of classical PID diseases and only 23.7% predominant antibody deficiency (prevalence of PID of 1.1 per 100000 children, genetic diagnosis of 36.6%, parental consanguinity of 61.1%)[40].…”
mentioning
confidence: 99%
“…The only countries in the Asia Pacific with national PID registries are Japan, South Korea, Taiwan, Hong Kong, and China (49). The Middle East countries with national PID registries are Kuwait, Turkey, and Iran (5,50,51). There was an increase in reporting over time which may be attributed to the increase in numbers of practicing clinical immunologists, enhanced diagnostic strategies, and facilities and improved awareness amongst medical fraternities locally (52).…”
Section: Discussionmentioning
confidence: 99%